The - 55 C/T polymorphism within the UCP3 gene and performance during the South African Ironman Triathlon - Hudson, D. E.; Mokone, G. G.; Noakes, T. D.; Collins, M. (International Journal of Sports Medicine, 2004)
Uncoupling protein 3 is believed to be involved in total body energy expenditure, including the regulation of fat and glucose metabolism. These biochemical processes may distinguish top ultra-endurance triathletes from slower competitors. The aim of this study was to determine whether the uncoupling protein 3 gene is associated with the performance capacity of ultra-endurance Ironman triathletes. Two triathlete groups consisting of the 89 fastest and 89 slowest Caucasian, male triathletes who completed either the 2000 or 2001 South African Ironman triathlon events were genotyped for the - 55 C/T polymorphism within the uncoupling protein 3 gene. A control group consisting of 92 Caucasian males who had not trained for or participated in an ultra-endurance athletic event was also genotyped. There was no significant difference in the genotype (CC, CT and TT) frequency distribution of the - 55 C/T polymorphism within the uncoupling protein 3 gene between the fast triathlete, slow triathlete and control groups. In addition, no significant differences were observed between the frequencies of the C and T alleles between the three groups. The two triathlete groups were combined and grouped according to their genotype. No particular genotype or allele was associated with the time taken by the triathletes to complete the entire triathlon, or either the swim, cycle or run legs of the event. Thus no association was found between the - 55 C/T polymorphism within the uncoupling protein 3 gene and the ultra-endurance performance of triathletes who completed either the 2000 or 2001 South African Ironman triathlons.